2017
DOI: 10.1038/nm.4345
|View full text |Cite
|
Sign up to set email alerts
|

Metformin alters the gut microbiome of individuals with treatment-naive type 2 diabetes, contributing to the therapeutic effects of the drug

Abstract: Metformin is widely used in the treatment of type 2 diabetes (T2D), but its mechanism of action is poorly defined. Recent evidence implicates the gut microbiota as a site of metformin action. In a double-blind study, we randomized individuals with treatment-naive T2D to placebo or metformin for 4 months and showed that metformin had strong effects on the gut microbiome. These results were verified in a subset of the placebo group that switched to metformin 6 months after the start of the trial. Transfer of fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

75
1,141
10
43

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,302 publications
(1,326 citation statements)
references
References 72 publications
75
1,141
10
43
Order By: Relevance
“…Studies have proposed various mechanisms of action for metformin to reduce gluconeogenesis in the liver (5) or via affecting the gut microbiota (30), reporting mainly indirect effects of metformin through various pathways involved in the metabolic control. Thus far, only Madiraju et al (6) and this study have revealed tissue-specific, direct cellular targets of metformin, mtGPD in liver, and SHIP2 in muscle and kidney, contributing to the effect of metformin to reduce gluconeogenesis and increase glucose uptake, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proposed various mechanisms of action for metformin to reduce gluconeogenesis in the liver (5) or via affecting the gut microbiota (30), reporting mainly indirect effects of metformin through various pathways involved in the metabolic control. Thus far, only Madiraju et al (6) and this study have revealed tissue-specific, direct cellular targets of metformin, mtGPD in liver, and SHIP2 in muscle and kidney, contributing to the effect of metformin to reduce gluconeogenesis and increase glucose uptake, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…143 In a recent RCT of 40 patients with type 2 diabetes, metformin altered the composition of gut microbiota by increasing the abundance of Escherichia and Bifidobacterium and decreasing the abundance of Intestinibacter, thereby increasing production of SCFAs. 144 …”
Section: Othersmentioning
confidence: 99%
“…There is convincing evidence [19,20] that metformin exposure induces significant changes in human intestinal microbiota (for example, decreases in abundance of Intestinibacter), and in the gut metabolome (for example, increased butyrate production). These observations stemmed from efforts to confirm and extend prior research (for examples, [21][22][23]) concerning relationships between microbiota composition, obesity and diabetes.…”
Section: Metformin and Gut Microbiotamentioning
confidence: 99%